Guideline‐Recommended Therapies and Clinical Outcomes According to the Risk for Recurrent Cardiovascular Events After an Acute Coronary Syndrome. Issue 18 (18th September 2018) - Hammer, Yoav; Iakobishvili, Zaza; Hasdai, David; Goldenberg, Ilan; Shlomo, Nir; Einhorn, Michal; Bental, Tamir; Witberg, Guy; Kornowski, Ran; Eisen, Alon
Abstract : Background: Patients who have had an acute coronary syndrome (ACS) are at increased risk of recurrent cardiovascular events; however, paradoxically, high‐risk patients who may derive the greatest benefit from guideline‐recommended therapies are often undertreated. The aim of our study was to examine the management, clinical outcomes, and temporal trends of patients after ACS stratified by the Thrombolysis in Myocardial Infarction (TIMI) risk score for secondary prevention, a recently validated clinical tool that incorporates 9 clinical risk factors. Methods and Results: Included were patients with ACS enrolled in the biennial Acute Coronary Syndrome Israeli Surveys (ACSIS) between 2008 and 2016. Patients were stratified by the TIMI risk score for secondary prevention to low (score 0–1), intermediate (2), or high (≥3) risk. Clinical outcomes included 30‐day major adverse cardiac events (death, myocardial infarction, stroke, unstable angina, stent thrombosis, urgent revascularization) and 1‐year mortality. Of 6827 ACS patients enrolled, 35% were low risk, 27% were intermediate risk, and 38% were high risk. Compared with the other risk groups, high‐risk patients were older, were more commonly female, and had more renal dysfunction and heart failure ( P <0.001 for each). High‐risk patients were treated less commonly with guideline‐recommended therapies during hospitalization (percutaneous coronary intervention) and at discharge (statins, dual‐antiplatelet therapy, cardiac rehabilitation). Overall, high‐risk patients had higher rates of 30‐day major adverse cardiac events (7.2% low, 8.2% intermediate, and 15.1% high risk; P <0.001) and 1‐year mortality (1.9%, 4.6%, and 15.8%, respectively; P <0.001). Over the past decade, utilization of guideline‐recommended therapies has increased among all risk groups; however, the rate of 30‐day major adverse cardiac events has significantly decreased among patients at high risk but not among patients at low and intermediate risk. Similarly, the 1‐year mortality rate has decreased numerically only among high‐risk patients. Conclusions: Despite an improvement in the management of high‐risk ACS patients, they are still undertreated with guideline‐recommended therapies. Nevertheless, the outcome of high‐risk patients after ACS has significantly improved in the past decade, thus they should not be denied these therapies.